Production and activity of cellulase from Aspergillus niger using rice bran and orange peel as substrates - Oloyede, O.B, Abubakar, F.A (International Journal of Scientific Research and Management (IJSRM), 2013)
The production and factors controlling the activity of celluloytic enzyme secreted by Aspergillus niger in submerged culture with rice bran, orange peel, and Carboxymethylcellulose (control) as substrate was studied. The effects of pH, temperature and substrate concentrations on the enzyme activity were also studied. Optimal cellulase secretion was achieved in 94 hours of growth in rice bran, and Carboxymethylcellulose with cellulase activities as 16.63μmol/ml, and 3.61μmol/min respectively. Within the growth period of 48 hours, cellulase activity of 14.30 mol/min was observed in orange peel. Substrate concentration of 6 and 8% w/v favoured the cellulase activity. While pHs 3 and 4 produced optimal enzyme secretion. Also temperatures of 45ºC and 50ºC favoured cellulase production.